Analysis of causes and strategies to reduce student misconceptions in science subjects at elementary school - Adilah, Nur; Ngazizah, Nur; Nurhidayati, Nurhidayati (Univeritas Papua, 2025)
This research is motivated by many students who feel they have understood magnetic material, but when the teacher conducts a test on magnetic material, low scores are obtained. This is certainly a challenge for teachers to teach magnetic material better so that students can understand it. This study aims to analyze students' misconceptions in learning science magnetic material at the elementary school level using the CRI (certainty of response index) method, which consists of 4 categories, namely MN (guessing), PK (understanding the concept), TPK (not understanding the concept), and M (misconception). This research uses a descriptive qualitative method to analyze the causes and solutions of misconceptions about magnetic material in depth. Data was collected through observation, interviews, and the CRI test. The results of the study stated that misconceptions were caused by students' preconceptions and imperfect understanding. In addition, this study found a link between concept understanding and misconceptions. Students who have low understanding tend to experience high misconceptions. Therefore, the ideal learning strategy in accordance with student characteristics is a conceptual learning model combined with interactive learning media.